In vitro-synthesized hepatitis delta virus RNA initiates genome replication in cultured cells. - Glenn, J S (1990)
Monomers of the genomic strand of hepatitis delta virus RNA were transcribed in vitro and then delivered to NIH 3T3 fibroblasts by using a liposome fusion technique. After 7 days, genome replication was detected, but only in fibroblasts that stably expressed the delta antigen. Sequence analysis of the replicated products identified them as faithful copies of the hepatitis delta virus genome found in virions.